Characterization of the Sorbitol Utilization Cluster of the Probiotic Pediococcus parvulus 2.6: Genetic, Functional and Complementation Studies in Heterologous Hosts - Pérez-Ramos, Adrian; Werning, Maria L.; Prieto, Alicia; Russo, Pasquale; Spano, Giuseppe; Mohedano, Mari L.; López, Paloma (Frontiers in Microbiology, 2017)
Pediococcus parvulus 2.6 secretes a 2-substituted (1,3)-β-D-glucan with prebiotic and immunomodulatory properties. It is synthesized by GTF glycosyltransferase using UDP-glucose as substrate. Analysis of the P. parvulus 2.6 draft genome revealed the existence of a sorbitol utilization cluster of six genes (gutFRMCBA), whose products should be involved in sorbitol utilization and could generate substrates for UDP-glucose synthesis. Southern blot hybridization analysis showed that the cluster is located in a plasmid. Analysis of metabolic fluxes and production of the exopolysaccharide revealed that: (i) P. parvulus 2.6 is able to metabolize sorbitol, (ii) sorbitol utilization is repressed in the presence of glucose and (iii) sorbitol supports the synthesis of 2-substituted (1,3)-β-D-glucan. The sorbitol cluster encodes two putative regulators, GutR and GutM, in addition to a phosphoenolpyruvate-dependent phosphotransferase transport system and sorbitol-6-phosphate dehydrogenase. Therefore, we investigated the involvement of GutR and GutM in the expression of gutFRMCBA. The promoter-probe vector pRCR based on the mrfp gene, which encodes the fluorescence protein mCherry, was used to test the potential promoter of the cluster (Pgut) and the genes encoding the regulators. This was performed by transferring by electrotransformation the recombinant plasmids into two hosts, which metabolize sorbitol: Lactobacillus plantarum and Lactobacillus casei. Upon growth in the presence of sorbitol, but not of glucose, only the presence of Pgut was required to support expression of mrfp in L. plantarum. In L. casei the presence of sorbitol in the growth medium and the pediococcal gutR or gutR plus gutM in the genome was required for Pgut functionality. This demonstrates that: (i) Pgut is required for expression of the gut cluster, (ii) Pgut is subjected to catabolic repression in lactobacilli, (iii) GutR is an activator, and (iv) in the presence of sorbitol, trans-complementation for activation of Pgut exists in L. plantarum but not in L. casei.